Urate-lowering effects of dipeptidyl peptidase-4 inhibitors - Taras S. Panevin; Olga V. Zhelyabina; Maxim S. Eliseev; Marina V. Shestakova (Сахарный диабет)
Hyperuricemia is an increase of uric acid (UA) concentration in blood serum >420 pmol/L in men or >360 pmol/L in women and is considered to be a common biochemical abnormality. This condition shows that the extracellular fluid is oversaturated with urates, which concentration exceeds the limit of their solubility. This fact predisposes to the formation of crystals of sodium salt of UA and results in gout, urolithiasis, and other diseases. The frequent combination and relationship between purine and carbohydrate metabolism were noted in previous studies. In this regard, the choice of drugs for correcting these disorders should consider the possibility of a combined positive effect on the UA and serum glucose levels. The hypoglycemic drugs with pleiotropic effects on several metabolic syndrome components are considered to be of particular interest. Currently, one of the most frequently prescribed groups of drugs in the treatment of diabetes mellitus type 2 are dipeptidyl peptidase-4 inhibitors, which affect the level of incretins (gliptins). These drugs can be potentially attractive in patients with purine metabolism disorders since the available data indicate that these drugs affect UA level.